2020
DOI: 10.1186/s12903-020-1045-5
|View full text |Cite
|
Sign up to set email alerts
|

Women’s economic empowerment, participation in decision-making and exposure to violence as risk indicators for early childhood caries

Abstract: Objectives: In view of the association between early childhood caries (ECC])and maternal social risk factors, this study tried to determine if there were associations between indicators of processes, outputs and outcomes of women's empowerment, and the prevalence of ECC. Methods: In this ecological study, indicators measuring the explanatory variables-economic empowerment, decision-making and violence against women-were selected from the Integrated Results and Resources Framework of the UN-Women Strategic Plan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 63 publications
0
16
0
Order By: Relevance
“…Previous studies in Ethiopia [ 29 ] and Nigeria [ 30 ] reported similar findings. It is possible that women who had decision-making power would have opportunities to move and access information through their social networks [ 57 59 ]. Decision making power is an important concept for the woman herself and the society because the combination of access capabilities and actions shape whether women have influence over the decisions about their private lives, their health, and the health of their children and family [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in Ethiopia [ 29 ] and Nigeria [ 30 ] reported similar findings. It is possible that women who had decision-making power would have opportunities to move and access information through their social networks [ 57 59 ]. Decision making power is an important concept for the woman herself and the society because the combination of access capabilities and actions shape whether women have influence over the decisions about their private lives, their health, and the health of their children and family [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Caries is a complex process that is initiated by acids produced by bacterial metabolism of fermentable carbohydrates [ 11 ], and influenced by a range of biological and behavioural, social and wider contextual factors [ 11 , 16 ]. For instance, caries development and progression is affected by individual’s behaviours such as sugar consumption, oral hygiene practices and dental attendance as well as social and wider contextual factors such as socioeconomic status [ 17 – 19 ], women’s empowerment and participation in decision making in the community [ 20 ] and political status in the country [ 21 ]. This may explain the worldwide variations in caries distribution and aetiology [ 19 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…This evidence of increased child protection by mothers who have a history of sexual violence may also be reflected in the improved oral healthcare the children receive. There is however, research that demonstrated negative psychosocial impact of sexual violence with negative implications for the oral health of children 66 while another found no association between women’s experience of violence and ECC 67 . This finding needs to be studied further.…”
Section: Discussionmentioning
confidence: 97%